Development of a Sensitive Diagnostic Assay for Parkinson Disease Quantifying α-Synuclein–Containing Extracellular Vesicles. (4th May 2021) - Hong, Zhen; Tian, Chen; Stewart, Tessandra; Aro, Patrick; Soltys, David; Bercow, Matt; Sheng, Lifu; Borden, Kayla; Khrisat, Tarek; Pan, Catherine; Zabetian, Cyrus P.; Peskind, Elaine R.; et al.
Abstract : Objective: To develop a reliable and fast assay to quantify the α-synuclein (α-syn)–containing extracellular vesicles (EVs) in CSF and to assess their diagnostic potential for Parkinson disease (PD). Methods: A cross-sectional, multicenter study was designed, including 170 patients with PD and 131 healthy controls (HCs) with a similar distribution of age and sex recruited from existing center studies at the University of Washington and Oregon Health and Science University. CSF EVs carrying α-syn or aggregated α-syn were quantified using antibodies against total or aggregated α-syn, respectively, and highly specific, sensitive, and rapid assays based on the novel Apogee nanoscale flow cytometry technology. Results: No significant differences in the number and size distribution of total EVs between patients with PD and HCs in CSF were observed. When examining the total α-syn–positive and aggregated α-syn–positive EV subpopulations, the proportions of both among all detected CSF EVs were significantly lower in patients with PD compared to HCs ( p < 0.0001). While each EV subpopulation showed better diagnostic sensitivity and specificity than total CSF α-syn measured directly with an immunoassay, a combination of the 2 EV subpopulations demonstrated a diagnostic accuracy that attained clinical relevance (area under curve 0.819, sensitivity 80%, specificity 71%). Conclusion: Using newly established, sensitive nanoscale flow cytometry assays, we have demonstrated that total α-syn–positive and aggregated α-syn–positive EVs in CSF may serve as a helpful tool in PD diagnosis. Classification of Evidence: This study provides Class III evidence that total and aggregated α-syn–positive EVs in CSF identify patients with PD.